Case Report: Clinical and Imaging Characteristics of a Patient with Anti-flotillin Autoantibodies: Neuromyelitis Optica or Multiple Sclerosis? - Shang, Ke; Cheng, Chang; Qin, Chuan; Xiao, Jun; Deng, Gang; Bu, Bi-Tao; Xu, Sha-Bei; Tian, Dai-Shi (Frontiers in Immunology, 2021)
Background Demyelination diseases are complex puzzles that are not always straightforward to diagnose. Multiple sclerosis and neuromyelitis optica are two that are frequently encountered. Numerous autoantibodies newly discovered in recent years have significantly aided clinical reasoning and diagnosis in differentiating demyelination disorders. Here we report a case of demyelination disease with anti-flotillin autoantibodies positive, which is not common in past references. Case summary The patient presented with characteristic neuromyelitis optica symptoms and had remission and relapse. But his images exhibited characteristics of both neuromyelitis optica spectrum illness and multiple sclerosis. Conclusion This is the first case report describing the clinical course and imaging characteristics of demyelination illness associated with anti-flotillin autoantibodies. Although so far it appears to be a subtype of multiple sclerosis, there is still a potential that it is separate from MS and NMOSD.